JAK2-STAT3 signaling: A novel function and a novel mechanism - Hofmann, Hans-Dieter (Landes Bioscience, 2012)
The function of JAK-STAT signaling in the central nervous system has been widely studied in the context of neural cell development and differentiation and in neuronal and glial responses to CNS injury. A study published recently in Neuron by Nicolas et al. now demonstrates that the JAK2-STAT3 pathway also plays an important role in the regulation of synaptic transmission. By using a combination of biochemical, pharmacological and genetic approaches they show that induction of long-term depression (LTD), an activity-dependent rapid and long-lasting decrease in synaptic strength, via NMDA receptors depends on STAT3 activation by JAK2 that can be localized specifically to postsynaptic structures. Most interestingly, they find that induction of LTD requires STAT3 phosphorylation and dimerization but is independent of nuclear translocation and transcriptional activity of STAT3. Although it remains to be clarified how NMDA receptor-mediated postsynaptic processes lead to JAK2-STAT3 activation and how this in turn translates into persistent changes in synaptic strength, these results provide evidence for a novel mechanism of signal transduction.